PENGELOMPOKAN BIDANG LAJU PERTUMBUHAN EKONOMI INDONESIA MENGGUNAKAN ALGORITMA K-MEANS - Amril Mutoi Siregar (Universitas Ma'soem, 2019)
Indonesian is one of countries with economic development in the very good category. Economic growth is seen from several supporting fields, Indonesia has a lot of excess natural resources, which can support the economy compared to other countries. But the problem faced is the lack of maximum management of the economy, Indonesia has economic support categorized into 17 fields. Among the fields not in the same development because they are still stuck in one area, it turns out that Indonesia has all the potential to improve all fields. To increase the growth of all fields, the government must have correct, accurate and relevant data to group these fields. In this study using the Decision Tree algorithm to classify fields supporting economic growth automatically. The grouping results into three classes, namely high, medium, low. After the research was conducted the results were that the high category group was Mining and Excavation, Construction, transportation and warehousing, Provosion of accommodation and food Drinking, Information and Communication, Financial Services and Insurance, Real Estate, Educational Services, Health Services and Social Activities, medium groups were Procurement of Electricity and Gas, Company Services and low-income groups are in the fields of Agriculture, Forestry, and Fisheries, Processing Industry, water supply , waste management, Waste and Recycling, large Trade and retail, car and motorcycle repair, Government Administration, Defense and Compulsory Social Security, Other Services.